Impact of a water-sediment regulation scheme on nutrient variations at the Lijin station of the Yellow River - Li, Chang; Wang, Zhili; Liu, Huaixiang; Zuo, Liqin; Lu, Yan; Wu, Pan; Lu, Yongjun (Frontiers in Environmental Science, 2022)
The water-sediment regulation scheme (WSRS) imposed on dams throughout the Yellow River not only alleviates siltation in the downstream section but also alters the nutrient characteristics, which indirectly affects the enrichment of nutrients in the estuary. Nevertheless, the long-term changes in the nutrient contents and their causes in the lower Yellow River (LYR) remain unclear, and the nutrients characteristics during the years with and without WSRS have yet to be compared. Therefore, the purpose of this study was to explore the variations in the nutrient contents and limitations at the Lijin station on the LYR over the past decade, especially during the annual WSRS period, and to compare the water quality characteristics at Lijin between the years with and without WSRS. The results reveal that WSRS significantly changed the seasonal nutrient concentrations (nitrogen, phosphorus and silicon) at the Lijin station. The fluxes of these nutrients during WSRS (excluding 2016 and 2017) accounted for 11.64-40.63% of the total annual fluxes. The N concentration in the LYR was higher than that in some global rivers, while the concentrations of dissolved inorganic phosphorus (DIP) and dissolved silica (DSi) were lower than the average levels in other rivers. In addition, higher values of dissolved inorganic nitrogen (DIN), DSi and the Redfield ratio indicated that the growth of phytoplankton at the Lijin station was strongly restricted by P. However, during the two years without WSRS (2016 and 2017), the proportions of the nutrient fluxes in June were less than 66% of those in the WSRS period in other years. Additionally, there was a potential Si limitation in June in these two years. Furthermore, due to the occurrence of floods upstream of the Yellow River and the low-level operation of the Xiaolangdi Reservoir, the fluxes of nutrients during WSRS in 2018 were approximately 0.90-4.20 times those during the same period in 2009-2015 and 6.30-35.76 times those in June 2016 and June 2017. This study shows that WSRS effectively changes the nutrient balance in the LYR and provides a reference for the multi-objective collaborative optimization of WSRS to improve siltation and control flood in the LYR.